Design and Simulation of DC-AC Power Converters - Salam Waley Shneen (Peneliti Teknologi Teknik Indonesia, 2026)
Currently, various types of electronic power converters are used in many fields and industrial applications, one of the most important of which is industrial power converters. They are an essential part of electrical power systems in generating stations, distribution systems, and transmission systems, through their connection to the main grid and sub-grids. Electronic power converters are used in energy generation systems from sustainable development sources, and clean energy is a good example of this. The functions of electronic power converters vary according to the need for them, including changing the type of voltage, current, and frequency, which are electrical quantities. Electronic power converters can be classified into buck, step-down, boost, and step-up. The inverter is one of the types of electronic power converters that works to convert and change the converter input from direct current to a converter output with an alternating voltage. The input of the converter is connected to a DC source such as batteries, solar power, or a DC generator, while the output of the converter supplies AC loads such as a single-phase or three-phase induction motor. The inverter can be single-phase or three-phase, depending on the load to be supplied, and it can be a half-wave or full-wave bridge. The study contributes to implementing and setting appropriate design steps, in addition to building a simulation model to determine the system's behavior during a specific operating period.